A Model of Aerobic and Anaerobic Metabolism of Hydrogen in the Extremophile Acidithiobacillus ferrooxidans - Kucera, Jiri; Lochman, Jan; Bouchal, Pavel; Pakostova, Eva; Mikulasek, Kamil; Hedrich, Sabrina; Janiczek, Oldrich; Mandl, Martin; Johnson, D. Barrie (Frontiers in Microbiology, 2020)
Hydrogen can serve as an electron donor for chemolithotrophic acidophiles, especially in the deep terrestrial subsurface and geothermal ecosystems. Nevertheless, the current knowledge of hydrogen utilization by mesophilic acidophiles is minimal. A multi-omics analysis was applied on Acidithiobacillus ferrooxidans growing on hydrogen, and a respiratory model was proposed. In the model, [NiFe] hydrogenases oxidize hydrogen to two protons and two electrons. The electrons are used to reduce membrane-soluble ubiquinone to ubiquinol. Genetically associated iron-sulfur proteins mediate electron relay from the hydrogenases to the ubiquinone pool. Under aerobic conditions, reduced ubiquinol transfers electrons to either cytochrome aa3 oxidase via cytochrome bc1 complex and cytochrome c4 or the alternate directly to cytochrome bd oxidase, resulting in proton efflux and reduction of oxygen. Under anaerobic conditions, reduced ubiquinol transfers electrons to outer membrane cytochrome c (ferrireductase) via cytochrome bc1 complex and a cascade of electron transporters (cytochrome c4, cytochrome c552, rusticyanin, and high potential iron-sulfur protein), resulting in proton efflux and reduction of ferric iron. The proton gradient generated by hydrogen oxidation maintains the membrane potential and allows the generation of ATP and NADH. These results further clarify the role of extremophiles in biogeochemical processes and their impact on the composition of the deep terrestrial subsurface.